Activated Bledug Kuwu’s Clay as Adsorbent Potential for Synthetic Dye Adsorption: Kinetic and Thermodynamic Studies - Sri Lestari; Muflihah Muflihah; Ratna Kusumawardani; Mukhamad Nurhadi; Yuniati Mangesa; Fathur Insani Ridho; Robbiatul Adawiyah; Pristiningtyas Ambarwati; Siti Rahma; Sin Yuan Lai; Hadi Nur (Bulletin of Chemical Reaction Engineering & Catalysis, 2022)
Bledug Kuwu is one of the geological phenomena as a mud volcano that occurs in Kuwu, Purwodadi, Grobogan, Central Java, Indonesia. The evaluation of Bledug Kuwu’s clay as one of the adsorbents for synthetic dyes has been carried out. The preparation of the adsorbent started with washing the clay with distilled water, followed by activation with a solution of hydrochloric acid (1 M) under mechanistic stirring for overnight. The C−H and O−H groups found on the clay adsorbent could attract methylene blue by dispersion forces and hydrogen bonding. Hydrocloric acid activation process for clay can increase surface area from 49 to 70 m2.g−1, meanwhile, reducing the average crystal size from 48.3 to 43.4 nm. The dye removal capacity increased from 34 to 40 mg.g−1 in corresponding to the increase of the temperature from 30 to 50 °C. The results showed that the equilibrium adsorption capacity of activated Bledug Kuwu’s clay reached 99% in an adsorption time of 20 min. The kinetic models of methylene blue adsorption onto BKC and ABKC adsorbents follow the pseudo-second order and the adsorption process is spontaneous with free energy (ΔG) as −23.519 kJ.mol−1. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).